2019
DOI: 10.15446/profile.v21n1.69239
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teachers’ Perspectives on the Role of English in Two Mexican Private Universities

Abstract: In Mexican higher education, the spread of English has become a tool in the internationalization process of universities. However, language has been sidelined in the discourses of globalization and internationalization. Hence, this ethnographic case study aims to look at the spread of English in Mexican higher education through two private universities. It focuses on the universities’ internationalization process, and how English as a foreign language teachers perceive the role of English in this process. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Additionally, the literature from Latin America reiterates the dearth of research on emi and the need for specialized professional development addressed in the Spanish literature discussed above (Arias de la Cruz et al, 2019;Crawford et al, 2013;de la Barra et al, 2018;Despagne, 2019;Lara-Herrera et al, 2016;López & Puebla, 2014;Navas-Brenes, 2010;Rivera & Mazak, 2017;Vargas-Vásquez et al, 2016). It also exhibited the tendency of researchers to inquire into the perceptions of stakeholders about the implementation of emi (Despagne, 2019;Lara-Herrera et al, 2016;Rivera & Mazak, 2017;Vargas-Vásquez et al, 2016) rather than conducting empirical studies directly focused on instruction and learning.…”
Section: Emi Literature In the Latin-american Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the literature from Latin America reiterates the dearth of research on emi and the need for specialized professional development addressed in the Spanish literature discussed above (Arias de la Cruz et al, 2019;Crawford et al, 2013;de la Barra et al, 2018;Despagne, 2019;Lara-Herrera et al, 2016;López & Puebla, 2014;Navas-Brenes, 2010;Rivera & Mazak, 2017;Vargas-Vásquez et al, 2016). It also exhibited the tendency of researchers to inquire into the perceptions of stakeholders about the implementation of emi (Despagne, 2019;Lara-Herrera et al, 2016;Rivera & Mazak, 2017;Vargas-Vásquez et al, 2016) rather than conducting empirical studies directly focused on instruction and learning.…”
Section: Emi Literature In the Latin-american Contextmentioning
confidence: 99%
“…First of all, the Spanish and Latin-American literature mainly addresses emi in contexts where Spanish is spoken as a first language. The literature from both contexts assigns the popularity that emi has been gaining as to the desire that institutions and countries have to internationalize education and instill competences in students that would equip them to become competitive professionals globally (Arias de la Cruz et al, 2019;Crawford et al, 2013;de la Barra et al, 2018;Despagne, 2019;Lara-Herrera et al, 2016;López & Puebla, 2014;Navas-Brenes, 2010;Rivera & Mazak, 2017;Vargas-Vásquez et al, 2016). Additionally, the literature from Latin America reiterates the dearth of research on emi and the need for specialized professional development addressed in the Spanish literature discussed above (Arias de la Cruz et al, 2019;Crawford et al, 2013;de la Barra et al, 2018;Despagne, 2019;Lara-Herrera et al, 2016;López & Puebla, 2014;Navas-Brenes, 2010;Rivera & Mazak, 2017;Vargas-Vásquez et al, 2016).…”
Section: Emi Literature In the Latin-american Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…De la misma forma, el inglés se ha vuelto el centro de los programas de internacionalización de las universidades (Despagne, 2019). Por consiguiente, se ha adoptado su enseñanza a nivel nacional, aunque los resultados todavía parecen muy limitados.…”
Section: Situación Lingüística En Méxicounclassified
“…The learning of English in higher education has become a tool in the internationalization process for public and private universities (Despagne, 2019). The strength of the language policy showed that the university follows the guidelines of internationalization by promoting a high level of English competency, thereby favouring mobility.…”
Section: Analysis Of Official Documentsmentioning
confidence: 99%